A comparative study of preoperative and postoperative hearing after type I tympanoplasty using temporalis fascia graft at Dr. B. R. Ambedkar Medical College, Bengaluru - M., Muniraju; Hegde, Smita (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: The objective of the study was to identify the factors which significantly influence type 1 tympanoplasty success. Methods: A prospective study was performed on 30 patients who underwent type 1 tympanoplasty via underlay technique using temporalis fascia graft from December 2017 to September 2019 in a teaching hospital. Outcome measures were graft uptake rate and hearing gain. The factors assessed were the age and sex, preoperative condition of the ipsilateral and contralateral ears, perforation size, presence of tympanosclerosis, and whether simultaneous cortical mastoidectomy was performed. Results: None of the factors proved to have a significant influence on tympanic membrane closure or hearing gain. Conclusions: The success rate of a type 1 tympanoplasty is dependent on the skills of the surgeon and the type of graft used. Age, sex, laterality of the disease, duration of dry ear, size of the perforation, presence of tympanosclerosis and simultaneous cortical mastoidectomy have no bearing on hearing gain.